Gambaran Tingkat Stres dan Gejala Sindrom Pramenstruasi pada Mahasiswi Fakultas Kedokteran - Aisha Nadhira; Yuniarti; Winni Maharani Mauliani (UNISBA Press, 2024)
Abstract. Premenstrual syndrome is a condition that includes several physical and psychological symptoms and occurs before the menstrual phase. This condition occurs in women, especially during the reproductive age. The prevalence of premenstrual syndrome is in the age range of 16-45 years, and in Indonesia, around 85% of adolescents in the total reproductive age population experience premenstrual syndrome. One of the factors influencing premenstrual syndrome symptoms is the level of stress. The aim of this study is to determine the level of stress and premenstrual syndrome symptoms in female students at the Faculty of Medicine, Islamic University of Bandung. This research uses a descriptive method. The data subjects are female students of the Faculty of Medicine, Islamic University of Bandung, in the 1st-3rd year of the 2022-2023 academic year, with a total of 102 respondents. Data were obtained from the completion of questionnaires for stress levels and premenstrual syndrome symptoms. Data analysis used univariate tests. The results of this study show that 59 students (58%) experience moderate stress levels, and 50 students (85%) have premenstrual syndrome symptoms. The high level of activity and academic burden on medical students results in an increasingly severe level of stress experienced. Abstrak. Sindrom pramenstruasi merupakan suatu kondisi yang meliputi beberapa gejala fisik dan psikologis dan terjadi sebelum fase menstruasi. Kondisi ini terjadi pada perempuan terutama pada usia produktif. Prevalensi kejadian sindrom pramenstruasi ini berada pada usia 16-45 tahun dan di Indonesia sekitar 85% remaja dari total populasi usia reproduksi mengalami sindrom pramenstruasi. Salah satu faktor yang mempengaruhi gejala sindrom pramenstruasi adalah tingkat stres. Tujuan penelitian ini adalah mengetahui tingkat stres dan gejala sindrom pramenstruasi pada mahasiswi Fakultas Kedokteran Universitas Islam Bandung. Penelitian ini menggunakan metode deskriptif. Subjek data adalah mahasiswi Fakultas Kedokteran Universitas Islam Bandung tingkat 1-3 tahun ajaran 2022-2023 dengan jumlah responden 102 orang. Data diperoleh dari pengisian kuesioner untuk tingkat stres dan gejala sindrom pramenstruasi. Analisis data menggunakan uji univariat. Hasil penelitian ini menunjukan bahwa sebanyak 59 mahasiswi (58%) mengalami tingkat stres sedang dan 50 mahasiswi (85%) memiliki gejala sindrom pramenstruasi yang berat. Tingginya aktivitas dan beban akademik pada mahasiswi kedokteran mengakibatkan tingkat stres yang dialami semakin berat.